The Disappointment (1767): America's First Ballad Opera - Adler, Samuel 1928-; Eastman Philharmonia Chamber Ensemble (Rochester, NJ, USA) (New York Vox, 1976)
The Disappointment, or The Force of Credulity is a ballad opera composed by Samuel Adler in two acts with a prologue and epilogue, to a text by an unknown author writing under the pseudonym "Andrew Barton". William Peterson, in 1766, claimed that the opera was written by a "son of Philadelphia College," leading to speculation that the author may have been Francis Hopkinson or Jacob Duché.[2] In his book on American drama, Walter Meserve claims that the author was named Thomas Forrest. Regarded as one of the first American operas, it was to have been performed on April 20, 1762 in Philadelphia but was cancelled at the last moment.Samuel Adler reconstructed the score for a performance on October 29, 1976 at the Library of Congress in Washington, as part of the Bicentennial celebrations of the United States of America. A critic published a lukewarm review of the performance at the time.
Keywords: 20th Century (1901-2000); Forgery; Opera; Philadelphia (PA, USA)